PASTIKAN SUKSESNYA ERA PENDIDIKAN BARU: Pelatihan Virtual Meeting untuk Guru dan Tata Usaha di SMK - Henry Eryanto; Marsofiyati; Roni Faslah; Ponco Dewi Karyaningsih; Maulana Amirul Adha; Puji Wahono; Muhammad Alfian (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract Vocational education at the secondary level, such as vocational schools (SMK), plays a crucial role in preparing students for the workforce with relevant competencies. However, in the midst of the COVID-19 pandemic, SMK Walisongo 2 in Depok, West Java, faced challenges in adapting to the implementation of education. One solution adopted in the world of education is the use of virtual meetings for learning and meetings. The literature review describes the understanding, types of meetings, meeting requirements, meeting objectives, meeting procedures, meeting etiquette, communication styles in meetings, and meeting organization techniques. The method of implementing community service involves mentoring and training to achieve the desired outcomes. The results of the Office Administration Competency Training program for students and teachers at SMK in Parung, West Java, include understanding the material, discussions, and practical application. The conclusion of this activity is the improvement of competence in office administration for students and teachers. Recommendations provided include continuing efforts to develop competence in this field. Thanks to Universitas Negeri Jakarta and SMK 2 Walisongo Depok for their financial support and collaboration in the success of this program. Keywords: meeting; administration; virtual meeting. Abstrak Pendidikan kejuruan di tingkat menengah, seperti SMK, memiliki peran krusial dalam mempersiapkan peserta didik untuk dunia kerja dengan kompetensi yang relevan. Namun, di tengah pandemi COVID-19, SMK Walisongo 2 di Depok, Jawa Barat, harus menghadapi tantangan adaptasi dalam pelaksanaan pendidikan. Salah satu solusi yang telah diadopsi di dunia pendidikan adalah penggunaan virtual meeting untuk pembelajaran dan pertemuan. Tinjauan literatur menggambarkan pengertian, jenis-jenis rapat, syarat-syarat rapat, tujuan rapat, tata tertib rapat, etika dan gaya komunikasi dalam rapat, serta teknik penyelenggaraan rapat. Metode pelaksanaan pengabdian kepada masyarakat melibatkan pendekatan pendampingan dan pelatihan untuk mencapai luaran yang diinginkan. Hasil program pelatihan Kompetensi Administrasi Perkantoran bagi Siswa dan Guru SMK di Parung, Jawa Barat, mencakup pemahaman materi, diskusi, dan penerapan dalam praktik. Kesimpulan dari kegiatan ini adalah peningkatan kompetensi siswa dan guru dalam administrasi perkantoran. Saran yang diberikan adalah melanjutkan upaya dalam pengembangan kompetensi di bidang ini. Terima kasih kepada Universitas Negeri Jakarta dan SMK 2 Walisongo Depok atas dukungan finansial dan kerjasamanya dalam kesuksesan program ini. Kata Kunci: rapat; administrasi; virtual meeting